2004
DOI: 10.1088/0022-3727/37/22/024
|View full text |Cite
|
Sign up to set email alerts
|

Production of iodine atoms by dissociating CH3I and HI in a dc glow discharge in the flow of argon

Abstract: The production of iodine atoms by means of glow discharge in gas flow, with a view to using them in chemical oxygen–iodine lasers, was studied. A dc glow discharge was sustained between coaxial electrodes in the vortex flow of argon, used as the carrier gas, with the addition of iodine-containing molecular precursors CH3I and HI.In the experiments a high atomic iodine concentration of more than 1016 cm−3 was achieved at a pressure of the Ar carrier of up to 30 Torr. The dissociation degree of the precursor mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…High iodine atom densities of ∼ 10 16 cm −3 have been achieved in dc glow discharges [36][37][38]. However, in achieving these densities through discharge, relatively high pressures (∼few tens of Torr) of both the precursor (I 2 , CH 3 I) and carrier gases (He, Ar) are required.…”
Section: Experimental Feasibility -mentioning
confidence: 99%
“…High iodine atom densities of ∼ 10 16 cm −3 have been achieved in dc glow discharges [36][37][38]. However, in achieving these densities through discharge, relatively high pressures (∼few tens of Torr) of both the precursor (I 2 , CH 3 I) and carrier gases (He, Ar) are required.…”
Section: Experimental Feasibility -mentioning
confidence: 99%
“…The alkyl halide was chosen over I as it is more convenient to handle, dissociates efficiently in discharges, and the fragmentation products do not quench I*. Mikheyev et al [86] have demonstrated 100% dissociation of CH I in this system. In tests where the discharge products were injected in to a cold primary flow (room temperature Ar), Azyazov et al [79,80] observed loss of I atoms due to homogeneous recombination.…”
Section: Iodine Dissociationmentioning
confidence: 99%
“…8. A distinguishing feature of this generator is the lower than usual electric field in the discharge plasma due to a small interelectrode gap of just 4 mm.…”
Section: A Iodine Atom Generatormentioning
confidence: 99%